2019
DOI: 10.3390/nu11020470
|View full text |Cite
|
Sign up to set email alerts
|

Energy Status and Body Composition Across a Collegiate Women’s Lacrosse Season

Abstract: Little data is available regarding the energy and nutritional status of female collegiate team sport athletes. Twenty female NCAA Division II lacrosse athletes (mean ± SD: 20.4 ± 1.8 years; 68.8 ± 8.9 kg; 168.4 ± 6.6 cm; 27.9 ± 3% body fat) recorded dietary intake and wore a physical activity monitor over four consecutive days at five different time points (20 days total) during one academic year. Body composition, bone health, and resting metabolic rate were assessed in conjunction with wearing the monitor du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 27 publications
(40 reference statements)
0
44
3
Order By: Relevance
“…Research conducted with 20 women training Lacrosse on different competitive season moment showed that only in one of the five phases of the study located at different periods during the season, the competitors exceeded the average energy availability of 30 kcal/kg fat free mass/day. However, in the remaining phases of the study these values were lower [39]. This study did not indicate how large the percentage of the study group did not reach these values though.…”
Section: Discussioncontrasting
confidence: 60%
“…Research conducted with 20 women training Lacrosse on different competitive season moment showed that only in one of the five phases of the study located at different periods during the season, the competitors exceeded the average energy availability of 30 kcal/kg fat free mass/day. However, in the remaining phases of the study these values were lower [39]. This study did not indicate how large the percentage of the study group did not reach these values though.…”
Section: Discussioncontrasting
confidence: 60%
“…In this respect, the predicted daily energy requirement that corresponded with the low activity level (40 kcal/kg of bodyweight) was similar to the mean (SD) measured TDEE of 37.9 ± 4.7 kcals/kg of bodyweight. This level of total daily energy expenditure appears to remain fairly consistent, even throughout the duration of a season in female lacrosse players [21] with average game energy expenditures ranging between 800 and 1000 kcals/game. Even when using a conservative “low” activity level to estimate energy requirements, the athletes in the current study still failed to meet energy requirements, as their mean energy intake was 32.1 ± 7.9 kcal/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have investigated the prevalence of low EA in various sports [8,[13][14][15][16][17][18][19][20][21][22]. Prevalence ranges from 22% to 58% (Table 1).…”
Section: Low Energy Availabilitymentioning
confidence: 99%